2001
DOI: 10.1054/bjoc.2001.1810
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of matrix-metalloproteinase-9 in human breast cancer: a potential favourable indicator in node-negative patients

Abstract: Summary Matrix metalloprotease-9 (MMP-9; 92 kDa type IV collaganase, gelatinase B) is regarded as, important for degradation of the basement membrane and extracellular matrix during cancer invasion and other tissue-remodelling events. In this study we evaluate the prognostic value of MMP-9, by immunoperoxidase staining in a series of 210 breast cancer tissues. The results were quantitated using the HSCORE system, which consider both staining intensity and the percentage of cells stained at given intensities. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
164
0
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(187 citation statements)
references
References 43 publications
13
164
0
10
Order By: Relevance
“…Subgroup analysis by location showed that a statistically significant impact of MMP-9 expression as a prognostic factor in both of tumor cells and stromal tissue. But we also noticed that some studies (Oscar et al, 2012;Tian et al, 2009;Vizosoet al, 2007;Li et al, 2006;Scorilas et al, 2001) combined the expression of tumor cells and stromal tissue to investigate the significance of MMP-9 expression, which made it difficult to explain which part of accumulation of MMP-9 played the most important influence on prognosis in breast cancer patients. Therefore, the impact of different location of MMP-9 expression on prognosis seems still needed to be further confirmed by adequately designed studies with multivariate analysis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Subgroup analysis by location showed that a statistically significant impact of MMP-9 expression as a prognostic factor in both of tumor cells and stromal tissue. But we also noticed that some studies (Oscar et al, 2012;Tian et al, 2009;Vizosoet al, 2007;Li et al, 2006;Scorilas et al, 2001) combined the expression of tumor cells and stromal tissue to investigate the significance of MMP-9 expression, which made it difficult to explain which part of accumulation of MMP-9 played the most important influence on prognosis in breast cancer patients. Therefore, the impact of different location of MMP-9 expression on prognosis seems still needed to be further confirmed by adequately designed studies with multivariate analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, two studies (Pellikainen 2004;Gonzalez et al, 2010) provided information about MMP-9 expression in tumor cells and stromal tissues respectively without general result, which we treated independently. Eventually, 15 studies met the inclusion criteria were included (Scorilas et al, 2001;Fan et al, 2003;Li et al, 2004;Pellikainen et al, 2004;Rahko et al, 2004;Li et al, 2006;Mylona et al, 2007;Vizoso et al, 2007;Feng et al, 2008;Wu et al, 2008;Zhao et al, 2008;Tian et al, 2009;Gonzalez et al, 2010;Sullu et al, 2011;Oscar et al, 2012).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In melanoma, increased expression of MMP-9 is found in the early steps, but at a later stage the opposite is true (van den Oord et al, 1997). In breast and colon cancer MMP-9 expression has been correlated with both increased and decreased survival and formation of distant metastasis (Pacheco et al, 1998;Scorilas et al, 2001;Takeha et al, 1997;Zeng et al, 1996). The current view is that the gelatinases and other MMPs are needed at multiple stages during the tumor progression and different tumors may utilize different MMPs.…”
Section: Gelatinases In Tumor Progressionmentioning
confidence: 99%
“…Moreover, MMP-9 was detected more frequently in malignant breast carcinoma than in benign tumour (Rha et al, 1997;Hanemaaijer et al, 2000). However, the role of MMP-9 is less clear than that of u-PA, as overexpression of MMP-9 in human breast cancer was reported to be a favourable indicator in node-negative patients (Scorilas et al, 2001).…”
Section: Cooperation Between Monocytes and Breast Cancer Cells E Blotmentioning
confidence: 99%